2011
DOI: 10.4236/fns.2011.25060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation on Total Phenolic Content and <i>in Vitro</i> Antioxidant Activity of Pomegranate (<i>Punica granatum</i> L.) Peels

Abstract: Pomegranate peels were studied for the effect of gamma irradiation on microbial decontamination along with its effect on total phenolic content and in vitro antioxidant activity. Gamma irradiation was applied at various dose levels (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 23 publications
(25 reference statements)
2
23
0
2
Order By: Relevance
“…Dessa forma, as amostras expostas à irradiação apresentaram maior estabilidade no decorrer do armazenamento. Mali et al (2011) avaliaram o efeito da irradiação em produtos obtidos de cascas de romã e observaram que as doses de irradiação de 5, 15 e 25 kGy não afetaram a concentração de compostos fenólicos, bem como não houve alterações significativas após um mês de armazenamento. No entanto, no mesmo estudo, a dose de 10 kGy proporcionou um aumento destes compostos, após 30 dias de armazenamento, assim como observado no presente estudo.…”
Section: Aranha J B Et Alunclassified
See 1 more Smart Citation
“…Dessa forma, as amostras expostas à irradiação apresentaram maior estabilidade no decorrer do armazenamento. Mali et al (2011) avaliaram o efeito da irradiação em produtos obtidos de cascas de romã e observaram que as doses de irradiação de 5, 15 e 25 kGy não afetaram a concentração de compostos fenólicos, bem como não houve alterações significativas após um mês de armazenamento. No entanto, no mesmo estudo, a dose de 10 kGy proporcionou um aumento destes compostos, após 30 dias de armazenamento, assim como observado no presente estudo.…”
Section: Aranha J B Et Alunclassified
“…Essa técnica é considerada um método efetivo na redução da contaminação microbiana, garantindo a segurança microbiológica do produto, bem como o aumento de sua vida útil (MALI et al, 2011).…”
Section: Introductionunclassified
“…(γ) Irradiation increased contents of phenolic acids in cinnamon and clove (Variyar, Bandyopadhyay, & Thomas, ). Mali, Khedkar, and Lele () and Ibrahim, Fawzy, Kamal, Sayed, and Mohammed () mentioned that irradiation increases phenolic compounds and antioxidant activity of pomegranate peel. Although some studies reported that γ irradiation can enhance the antioxidant activities, Alothman, Bhat, and Karim () and Sallam and Mervat () reported that (γ) irradiation decreases antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma irradiation was applied at various doses to date palm fruit Mazafati, and amount of total phenolic and antioxidant activity were increased significantly (Ghadi et al, 2015). Mali et al (2011) irradiated pomegranate peel and reported that gamma irradiation led to increase of total phenolic and antioxidant activity. Sima et al (2014) observed that methanol extract of Curcuma alismatifolia leaves increased total phenolic and antioxidant activity by gamma irradiation.…”
Section: Introductionmentioning
confidence: 99%